Calcinosis cutis in a neonate with transient hypoparathyroidism - Nayak, Sitikantha; Mishra, Baikuntha Narayan; Joshi, Ranjit Kumar; Pahi, Prabin Prakash (International Journal of Contemporary Pediatrics, 2020)
Calcinosis cutis is a condition, where there is deposition of calcium salts in skin and subcutaneous tissue, seen often in the middle to elderly aged population and is rare in neonates and infants. There are many aetiological factors, but in neonates and infants it is mostly seen as complication of extravasation of intravenous calcium infusion or trauma. For uncomplicated cases supportive treatment has been advocated. Authors describe a case presented with calcinosis cutis, who was treated for transient hypoparathyroidism in neonatal period.